A Random-Dot Kinematogram for Web-Based Vision Research - Rajananda, Sivananda; Lau, Hakwan; Odegaard, Brian (Journal of open research software, 2018)
Web-based experiments using visual stimuli have become increasingly common in recent years, but many frequently-used stimuli in vision research have yet to be developed for online platforms. Here, we introduce the first open access random-dot kinematogram (RDK) for use in web browsers. This fully customizable RDK offers options to implement several different types of noise (random position, random walk, random direction) and parameters to control aperture shape, coherence level, the number of dots, and other features. We include links to commented JavaScript code for easy implementation in web-based experiments, as well as an example of how this stimulus can be integrated as a plugin with a JavaScript library for online studies (jsPsych).Keywords: Random-dot kinematogram, random dot motion, moving dot stimulus, web-based experiments, online experiments, visual psychophysics, vision research, visual stimuli, JavaScript, jsPsych